Influence of SHE (Safety, Hygiene, Environment) and Service Quality on Purchase Intention Mediated By Pricing Policy on Scheduled Domestic Airlines in Indonesia - Wardana, Aditya; Arafah, Willy; Usman, Bahtiar (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The aim of this research is to analyse the influence of SHE (safety, hygiene, and environment) and service quality on purchase intention, which mediates pricing policy on scheduled domestic airlines in Indonesia. This research was conducted by distributing questionnaires to consumers via Google Forms to 250 respondents containing demographic questions and 43 statement items. The research method used is hypothesis testing. We measured the respondents' answers using a Likert scale, scoring from one to five, use Smart-PLS version 3.0 software with multivariate analysis methods. Structural Equation Model (SEM). It is directly proven that there is a significant positive influence between service quality and purchase intention. However, SHE to purchase intention is not proven to have a significant effect. Meanwhile, based on indirect hypothesis testing, it is proven that there is a significant influence between service quality and purchase intention mediated by pricing policy. And SHE variables mediated by pricing policy do not have a significant influence on purchase intention. In this research, researchers have limitations that future researchers can develop further by adding new variables or using other research methods. As a conclusion, the researcher has provided suggestions that may be useful for other researchers.